Oxford international primary English workbook 4 - Danihel, Emma; Hearn, Izabella (Pakistan : Oxford University Press, 2022)
Oxford International Primary English Workbook 4 is a well-crafted, write-in workbook designed to enhance reading comprehension, writing, speaking, and listening skills for primary-level learners. Aligned with international and Pakistani curricula (including Oxford International Curriculum, IB PYP, and Pakistan$1 (Bs Single National Curriculum), it presents engaging thematic fiction and non-fiction texts, highlighted vocabulary, and structured activities. Each unit offers discussion prompts, writing workshops with models and frames, and opportunities for differentiation, making language development accessible to mixed-ability classrooms. The workbook also supports multimedia learning with eBook versions and audio recordings, enriching both classroom delivery and independent studys
Keywords: English - Text Book